مقارنة بين لغة قريش ولغة بعض القبائل العربية:دراسة نحوية كلاسيكية حول ظاهرة أكلوني البراغيث - Novel (PPPBA, 2025)
Classical Arabic did not develop as a uniform linguistic system, but rather formed thru the interaction of various Arabic tribal dialects before and after Islam. Quraysh Arabic gained legitimacy as the standard language because it was used in the Quran and supported by social and scholarly authority, while other tribal language forms remained documented in classical grammar literature. One important phenomenon in this context is the construction of 'akalūnī al-barāghīṯ, which is the use of a plural verb preceding a plural visible subject. This article aims to compare the Quraysh language and the language of some Arab tribes from a classical grammar perspective using a descriptive-qualitative linguistic approach. This research shows that the difference is not a grammatical error, but rather a dialectal variation that is scientifically recognized but not normalized in the standard grammar system. This finding confirms that the standardization of Arabic is the result of ideological and pedagogical selection, not merely structural linguistic considerations. The benefits of this research are to enrich the classical Arabic linguistic treasury by providing a systematic mapping of the relationship between the Quraysh dialect and the variations in the dialects of Arab tribes in terms of syntactic construction, morphology, and lexical choices. Keywords: Quraysh Arabic, Dialectal Variation, Verb–Subject Agreement.